Problematika Guru dalam Implementasi Kurikulum Merdeka pada Pembelajaran IPAS Kelas IV MI Al Fithrah Surabaya - Ficky Dewi Ixfina (Prodi PGMI Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
This study aims to describe the problems faced by teachers in implementing the Independent Curriculum in IPAS learning at MI Al Fithrah Surabaya. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, then analyzed thematically. The findings reveal three key issues: first, teachers’ understanding of the philosophical foundation of the Independent Curriculum remains limited to technical aspects without grasping its deeper meaning of “freedom to learn”; second, teachers’ pedagogical competence in integrating science and social studies, as well as in applying innovative learning models, remains underdeveloped; and third, institutional support and teachers’ adaptive strategies, including internal collaboration and the integration of tasawuf values, play a vital role in overcoming implementation barriers. This study concludes that the successful implementation of the Independent Curriculum requires a balance between philosophical understanding, pedagogical competence, and continuous institutional support.